A study of transitional space in Branislav Milenkovic’s architectural analysis - Bnin-Bninski, Anđelka (Arhitektura i urbanizam, 2026)
The subject of the paper is the transitional space in Branislav Milenkovic’s architectural analysis. The research starts from the assumption that Milenkovic’s approach to architectural analysis is characterized by a particular accuracy, and that the potential for its actualization is contained in the domain of design-driven research. The motive for this study stems from problems regarding the contemporary professional context in which architectural undertakings are simplified under the pressures of the global market economy and financial efficiency. In such circumstances, the creative, critical, and socially responsible engagement of an architect are challenged and reduced to the production of solutions, in the form of stable and clear responses to the spatial demands of the building industry. Therefore, this study emphasizes the particular importance of Milenkovic’s professional position, because it advocates a shift in focus from the precise formulation of architectural solutions to the problematization of dynamic relationships between space and its users; the transitional space is taken as a testing ground for examining the possibilities of thoughtful and critical action.The paper is a trans-disciplinary theoretical study that aims to critically examine the concept of transitional space as fundamental to the design process and architectural analysis. The analysis of the dynamics of the relationship between space and the user is articulated around contemporary theories of gesture; it includes significant authors and reference sources from the domains of architecture, philosophy and anthropology (Goetz, Benjamin, Ingold, Augé, Lefebvre, Evans). The aim of the study is to explore Milenkovic’s concept of transitional space as a principle of the dynamic relationship between the user’s gesture and the spatial gesture and thus, to offer a detailed understanding of Milenkovic’s transitional space through its complex analysis in relation to the theory of gesture. The ultimate goal of the paper is to examine, within the domain of theory, whether the concept of transitional space opens up the possibility for critical action in contemporary design research.
Keywords: Branislav Milenković, architectural analysis, transitional space, gestures of habitation, design-driven research